Correlates of HIV-TB co-infection and mental health of adults living in countries across sub-Saharan Africa: systematic review and meta-analysis protocol - Anthony Danso-Appiah; Mishael Yankey; Isaac Kojo Appiah; Welbeck Amoani Twum (BMJ Open)
Introduction HIV and tuberculosis (TB) are two of the most devastating disease conditions of public health concern globally. A co-infection of the two diseases poses serious health challenges to patients including mental health problems, ranging from mild to severe, with differing outcomes. This systematic review aims to assess the correlates of HIV-TB co-infection and mental health of adults living in sub-Saharan Africa.Methods and analysis We will conduct comprehensive database and non-database searches for studies (published and unpublished). We will search Google Scholar, PubMed, CINAHL, LILACS, JSTOR, Cochrane Library, SCOPUS, PsycINFO, HINARI and African Journals Online from inception to 31 May 2025, without restriction on language. We will also search the grey literature, including conference proceedings, preprint repositories, databases of dissertations, WHO and governmental databases. In the event where there is a need to contact experts and corresponding authors for further information, the review team will do so to enrich the content of the review. At least three reviewers will independently undertake study selection, data extraction and risk of bias assessment using validated tools. We will resolve discrepancies or disagreements through discussion. We will analyse dichotomous data as risk ratio, OR or proportion and continuous data as mean difference with their SD; all estimates will be presented with their 95% CI. Where applicable, we will determine SD from point estimates and the appropriate denominators assuming a binomial distribution. The magnitude of heterogeneity between the included studies will be assessed quantitatively using the index of heterogeneity (I2 statistic). The I2 values of 25%, 50% and 75% will be considered to represent low, moderate and significant heterogeneity. The significance of heterogeneity will be determined by the p value of the I2 statistic, and a p value of <0.05 will be considered as statistically significant. For studies with moderate to significant heterogeneity, the random-effects model will be used to obtain a pooled estimate of the outcome, and if heterogeneity is low, a fixed-effect model will be used.Ethics and dissemination This systematic review will collate secondary research based on publicly available published and unpublished studies, and no ethical approval is required. However, an eligible study with serious ethical issues will be excluded and the reasons for exclusion documented. The review findings will be shared with key stakeholders, health authorities, agencies involved in the mental health of persons living with HIV-TB (PLHTB) co-infection, social services providers and policy implementers. The findings will be presented at scientific conferences and symposia. The final review report will be in the form of a scientific paper in a high-impact factor peer-reviewed journal.PROSPERO registration number CRD42024572331.